A qualitative study of mathematical content knowledge and pedagogical content knowledge and self-perception in Moroccan context - Jamal Ahmichane; Mostafa El Mallahi; Youness Hadder (Institute of Advanced Engineering and Science, 2026)
Pre-service teachers’ (PSTs) tertiary training is essential to their development as competent educators and to their professional readiness. Teachers must acquire the ability to communicate mathematical material in a variety of ways. Teachers of excellence must be proficient in the relevant mathematics content knowledge (MCK) and possess a strong foundation in interacting successfully with students. This study on education has two objectives: looking into how secondary PSTs who take part in a mathematics teaching unit view themselves as they interact with and solidify their MCK, and investigating how these PSTs view and understand their “readiness” to take on such a task. 25 PSTs participating in postgraduate teacher preparation programs were given the pre-unit survey (Phase 1), whose answers were subject to an extensive analysis through a high level of evaluation using a framework assisting the researcher in identifying relationships among social phenomena, based on the similarities and differences that connect these phenomena. Self-reflections of participants revealed different levels of readiness to teach lower secondary students in mathematics. All participants emphasized the need to enhance their pedagogical content knowledge (PCK) and their MCK, and a very limited number of studied participants said they felt comfortable teaching mathematics. The study implies a significant issue with professional readiness and self-efficacy, and it recommends a need for earlier and more intensive practical experience integrated with strong mentorship. A number of implications for either policy or teacher training practice are proposed. This study will cover the main outcomes of Phase 1 in light of the body of current studies on preparing PSTs of mathematics.